2015
DOI: 10.9734/bbj/2015/16810
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Operating Conditions Affecting Microbiologically Influenced Corrosion of Mild Steel Exposed to Crude Oil Environments Using Response Surface Methodology

Abstract: This work was carried out in collaboration between all authors. Author SEA reviewed areas related to microorganism behavior, selected the best microorganism for corrosion studies. Authors KKS and AOA designed the experiments, selected the material used and discussed the experimental results.Author IOS gathered all the materials used for the work, reviewed articles, run simulations and documented experimental results. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The Predicted R-Squared of 0.940884 was in reasonable agreement with the Adjusted R-Squared of 0.935095 which indicated that the experimental data fitted better Xin and Saka [10]. Adequate Precision of 19.38 is above the desirable minimum value of 4 was reported by Salam et al [11].…”
Section: Calibration Of the Modelsupporting
confidence: 78%
“…The Predicted R-Squared of 0.940884 was in reasonable agreement with the Adjusted R-Squared of 0.935095 which indicated that the experimental data fitted better Xin and Saka [10]. Adequate Precision of 19.38 is above the desirable minimum value of 4 was reported by Salam et al [11].…”
Section: Calibration Of the Modelsupporting
confidence: 78%
“…This strategy can be used to optimize experimental results achieved by weight loss measurements and is, therefore, essential to any research in this area. RSM offers the possibility to significantly reduce the number of experiments required to fully evaluate the performance of inhibitors, thus minimizing the cost and duration of the experiment [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Coefficients in the model characterized by positive values denote a synergistic effect, whereas negative values indicate an antagonistic effect (26). Among the model factors, Con 2 and Temp 2 positively contribute to the formulation, whereas Tim 2 , Con×Temp, Con×Tim, and Temp×Tim exert a negative influence on the developed model.…”
Section: Resultsmentioning
confidence: 99%